A legal study of the health screening (chest x-ray) for migrant workers with reference to the Atomic Energy Licensing Act 1984 / Mohd Reduan Abdul Razak - Abdul Razak, Mohd Reduan (2017)
Migrant workers are required to undergo pre-employment health screening before their application for working permit or specifically known as the Visit Pass (Temporary Employment) can be approve by the Malaysian Immigration Department. This work permit will only be granted to migrant workers who certified as ‘FIT’ by medical practitioner whereby those who are certified “UNFIT” shall be repatriated. Chest X-Ray examination is a mandatory test in this medical examination. The role of Chest X-Ray examination is as a screening tool in the diagnosis of tuberculosis disease carried by migrant workers. Migrant workers have to undergo a two stage health screening process which is firstly in their home country before leaving for Malaysia and another one upon arrival. The main issue concern in this study is whether the second Chest X-Ray examination is justified under the Atomic Energy Licensing Act 1984 even though they have successfully had Chest X-Ray examination before in their home country. The methodologies used are the doctrinal research and the fieldworks studies are on the respondents who are enforcement officers and medical practitioner. From the study, it was observed that the Chest X-Ray examination is mainly as a public safeguard and not beneficial to the health of the migrant workers. This practice was redundant after the compulsory Biometric system which was established by Malaysian Immigration Department on 15th June 2016. Our practice still focusing on active tuberculosis compared to the Australian legal framework which totally believe on pre-migration medical examination and focusing on latent tuberculosis. The public safeguard is the main reason to justify the Chest X-Ray examination for migrant workers in pre-employment health screening.